Proteomics and expression studies on lipids and fatty acids metabolic genes in Isochrysis galbana under the combined influence of nitrogen starvation and sodium acetate supplementation. (September 2021) - Kaur, Simrat; Hérault, Josiane; Caruso, Aurore; Pencréac'h, Gaëlle; Come, Martine; Gauvry, Laurent; Claverol, Stéphane; Loiseau, Céline
Abstract: The marine alga Isochrysis galbana was grown under the integrated influence of nitrogen starvation and sodium acetate, specifically to understand the associated remodelling of the fatty acid profiles. This is the first comparative proteomics study under four different set of conditions namely nutrient sufficient, with/without sodium acetate and N-deficient with/without sodium acetate. A total set of 546 unique peptides were detected. Due to the addition of sodium acetate, 56 proteins were down-regulated and 7 proteins showed up-regulation respectively in the nutrient complete and the nitrogen starvation media. Both cell growth and docosahexaenoic acid (DHA) accumulation in the nutrient replete cultures were favoured by the addition of reduced carbon source in the form of sodium acetate. The 14 days old sodium acetate supplemented nitrogen starved cells showed highest amounts of total fatty acids and an over accumulation of the oleic acid. Of the seven key genes of the lipid and fatty acid metabolic pathway that were studied, the IgTeCe, IgFad12, and IgFad4 showed over expressions under nitrogen starvation. The gene expressions of lipases and desaturases involved in the fatty acids metabolism were not found to be correlated with the changes observed in the fatty acid profiles under the experimental conditions. This suggested the presence of an alternative metabolic route and/or possibly the variants of fatty acid desaturase genes in I. galbana which was beyond the scope of this study. A translational or post-translational control can not either be ignored. Graphical abstract: Unlabelled Image Highlights: Maximum cell density was achieved in mixotrophic cultures of Isochrysis galbana DHA accumulation was triggered during early stage of nitrogen starvation Acetate promoted DHA accumulation in old nutrient replete cultures Periplasmic L-amino acid oxidase protein is 39.4X in acetate fed N - cultures IgTeCe, Fad12 and Fad4 genes were highly expressed under nitrogen starvation